Oxide dispersion strengthened steel, preparation method and application thereof and steel product
By using main components such as Fe, Cr, Al and specific proportions of Zn, Mg, Cu and graphene nanooxide particles in oxide dispersion reinforced steel, combined with chemical vapor deposition and hot pressing sintering technology, the oxide particles are realized The uniform dispersion and high-temperature tensile strength increase solve the problems of insufficient high-temperature tensile strength and poor dispersion of traditional oxide dispersion reinforced steel.
Patent Information
- Application Number
- CN202411182446.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-10
AI Technical Summary
The high-temperature tensile strength of traditional oxide dispersive reinforced steel needs to be improved, and there are challenges in uniform dispersing oxide nanoparticles during the preparation process, making it difficult to achieve widespread application.
Using Fe, Cr and Al as the main components, combined with Zn, Mg, Cu and nano-oxide particles with graphene layers on the surface, the graphene layer is grown by chemical vapor deposition to reduce oxide particles. The surface energy of the film promotes its uniform dispersion in FeCrAl, avoids aggregation, and enhances the high-temperature tensile strength through molding treatment such as hot pressing and sintering.
It effectively improves the high-temperature tensile strength of oxide dispersive reinforced steel, while maintaining good thermal conductivity and creep resistance, solving the problem of poor aggregation and dispersion of oxide particles.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to an oxide dispersion strengthened steel, a preparation method and application thereof, and a steel product. Background Art
[0002] Oxide Dispersion Strengthened Steel (ODS steel) is a special steel material that improves its performance by evenly dispersing trace amounts of oxide particles in the steel matrix. It has the characteristics of high strength, good creep resistance, and excellent oxidation resistance. Applications include aerospace: used to manufacture high-temperature and high-load components, such as jet engine components; nuclear energy: as a structural material in nuclear reactors; energy industry: used for high-temperature and high-pressure equipment in the oil and gas industry, etc. However, the high-temperature tensile strength of conventional oxide dispersion strengthened steel needs to be further improved. Summary of the invention
[0003] Based on this, the present application provides an oxide dispersion strengthened steel with high high temperature tensile strength, a preparation method and application thereof, and steel products.
[0004] The technical solution of this application to solve the above technical problems is as follows.
[0005] In a first aspect, the present application provides an oxide dispersion strengthened steel, which comprises, by mass percentage, 9% to 15% of a first component, 5% to 15% of a second component, and the remainder Fe and unavoidable impurities;
[0006] wherein the first component comprises Cr;
[0007] The second component comprises the following components by mass percentage:
[0008] Zn 4%-8%, Mg 1%-4%, Cu 1%-3%, nanoparticles 15%-25% and the balance Al; the nanoparticles are oxide particles having a graphene layer on the surface.
[0009] In some embodiments, in oxide dispersion strengthened steel, the mass ratio of the first component to the second component is (1-2):1.
[0010] In some embodiments, in oxide dispersion strengthened steel, the mass of the nanoparticles accounts for 15% to 20% of the total mass of the second component.
[0011] In some embodiments, in the oxide dispersion strengthened steel, the second component includes the following components by mass percentage:
[0012] Zn 4.6%~6.5%, Mg 1.8%~2.9%, Cu 1.2%~1.9%, nanoparticles 15%~20% and the balance Al.
[0013] In some of the embodiments, in the oxide dispersion strengthened steel, the oxide particles include at least one of La2O3, Y2O3, Ce2O3, TiO2 and MgO.
[0014] In some of the embodiments, in the oxide dispersion strengthened steel, the particle size of the oxide particles is 10 nm to 30 nm, and the mass of the graphene layer is 40% to 60% of the total mass of the nanoparticles.
[0015] A second aspect of the present application provides a method for preparing oxide dispersion strengthened steel, comprising the following steps:
[0016] Providing powder raw materials according to the composition of the above oxide dispersion strengthened steel;
[0017] The powder raw materials are mixed and then molded.
[0018] In some embodiments, in the method for preparing oxide dispersion strengthened steel, the method for preparing the nanoparticles comprises the following steps:
[0019] A graphene layer is grown on the surface of the oxide particles by chemical vapor deposition.
[0020] In some embodiments, in the method for preparing oxide dispersion strengthened steel, the chemical vapor deposition includes a deposition stage and a growth stage, and the chemical vapor deposition satisfies at least one of the following characteristics:
[0021] (1) The atmosphere during the deposition stage is a mixed gas of methane, hydrogen and argon;
[0022] (2) The temperature of the deposition stage is 300°C to 400°C, and the growth time is 1 h to 3 h;
[0023] (3) The temperature of the growth stage is 1000°C to 1200°C, and the growth time is 1 h to 3 h.
[0024] In some of the embodiments, in the method for preparing oxide dispersion strengthened steel, the temperature of the forming process is 1000°C to 1400°C.
[0025] The third aspect of the present application provides the use of the above-mentioned oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above-mentioned preparation method in the preparation of steel products.
[0026] A fourth aspect of the present application provides a steel product, comprising the above-mentioned oxide dispersion-strengthened steel or the oxide dispersion-strengthened steel prepared by the above-mentioned preparation method.
[0027] Compared with the prior art, the oxide dispersion strengthened steel of the present application has the following beneficial effects:
[0028] The oxide dispersion strengthened steel of the present application has Fe, Cr and Al as main components, and is matched with Zn, Mg, Cu and nanoparticles in specific proportions. The nanoparticles are oxide particles with a graphene layer on the surface. The graphene layer on the surface of the oxide particles can effectively reduce the surface energy of the oxide particles, thereby effectively promoting the uniform dispersion of the oxide particles in FeCrAl, and can effectively weaken the grain boundary interaction between the oxide particles, thereby effectively avoiding the aggregation of the oxide particles. The components interact with each other in a specific proportion, and on the basis of ensuring the room temperature tensile strength, the high temperature tensile strength of the oxide dispersion strengthened steel is effectively improved.
[0029] At the same time, the oxide dispersion strengthened steel of the present application also has good thermal conductivity. DETAILED DESCRIPTION
[0030] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0031] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0034] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0035] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0036] FeCrAl alloy has good resistance to high-temperature oxidation, corrosion and radiation, but its low high-temperature strength and low thermal conductivity are the main factors restricting its further application.
[0037] Oxide dispersion strengthening is a method that uses oxide nanoparticles to improve the high temperature stability and mechanical strength of materials, but uniform dispersion of oxide nanoparticles during the preparation process remains a major challenge. Due to the large difference in physical and chemical properties between the oxide and the matrix, nanoparticles tend to aggregate and are difficult to achieve uniform distribution. Existing methods often involve complex process steps or cannot be widely used in commercial production.
[0038] ODS FeCrAl alloys have a very fine grain structure and their thermal conductivity is lower than that of similar melt-cast steels.
[0039] Graphene is a single-atomic-layer two-dimensional material with excellent mechanical properties and ultra-high thermal conductivity. It is an ideal reinforcing phase for metal-based composites. However, due to its poor wettability, it is very easy to agglomerate in the material matrix.
[0040] An embodiment of the present application provides an oxide dispersion strengthened steel, which comprises, by mass percentage, 9% to 15% of a first component, 5% to 15% of a second component, and the remainder Fe and unavoidable impurities;
[0041] wherein the first component comprises Cr;
[0042] The second component includes the following components by mass percentage:
[0043] Zn 4%~8%, Mg 1%~4%, Cu 1%~3%, nanoparticles 15%~25% and the balance Al; the nanoparticles are oxide particles with a graphene layer on the surface.
[0044] It can be understood that an embodiment of the present application provides an oxide dispersion strengthened steel, which comprises the following components by mass percentage:
[0045] Cr 9%~15%, Zn 0.23%~0.975%, Mg 0.09%~0.435%, Cu 0.06%~0.285%, nanoparticles 0.75%~3.75%, Al 3.935%~13.11%, and the rest are iron and inevitable impurities; nanoparticles are oxide particles with a graphene layer on the surface.
[0046] The oxide dispersion strengthened steel of the present application has Fe, Cr and Al as main components, and is matched with Zn, Mg, Cu and nanoparticles in specific proportions. The nanoparticles are oxide particles with a graphene layer on the surface. The graphene layer on the surface of the oxide particles can effectively reduce the surface energy of the oxide particles, thereby effectively promoting the uniform dispersion of the oxide particles in FeCrAl, and can effectively weaken the grain boundary interaction between the oxide particles, thereby effectively avoiding the aggregation of the oxide particles. The components interact with each other in a specific proportion, and on the basis of ensuring the room temperature strength, the high temperature tensile strength of the oxide dispersion strengthened steel is effectively improved.
[0047] At the same time, the oxide dispersion strengthened steel of the present application also has good thermal conductivity and creep resistance.
[0048] It can be understood that the oxide dispersion strengthened steel provided in the present application includes but is not limited to the first component, the second component, Fe and impurities, and may also contain other components. The remaining Fe refers to the Fe and impurities remaining after removing the first component, the second component and "other components" from the oxide dispersion strengthened steel.
[0049] It can be understood that in the oxide dispersion strengthened steel, the first component includes, but is not limited to, 9%, 9.2%, 9.5%, 9.8%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, and 15%, by mass percentage; the second component includes, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%; further, in the second component, Zn includes, but is not limited to, 4%, 4.2%, 4.6%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.5%, 6.8%, 7%, 7. .2%, 7.5%, 7.8%, 8%; Mg includes but is not limited to 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 2.9%, 3%, 3.2%, 3.5%, 3.8%, 4%; Cu includes but is not limited to 1%, 1.2%, 1.5%, 1.8%, 1.9%, 2%, 2.2%, 2.5%, 2.8%, 2.9%, 3%; nanoparticles include but are not limited to 15%, 16%, 17%, 18%, 18.5%, 19%, 19.5%, 20%, 21%, 22%, 23%, 24%, 25%; in some examples, it can be within the range constituted by any two of these point values as end values, the same below.
[0050] In some of the examples, in the oxide dispersion strengthened steel, the mass ratio of the first component to the second component is (1~2):1.
[0051] It can be understood that the mass ratio of the first component to the second component includes but is not limited to 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, and 2:1.
[0052] Optionally, the mass ratio of the first component to the second component is 1:1.
[0053] In some of these examples, the mass of nanoparticles in oxide dispersion strengthened steels accounts for 15% to 20% of the total mass of the second component.
[0054] It will be appreciated that the percentage of the mass of the nanoparticles to the total mass of the second component includes but is not limited to 15%, 15.2%, 15.5%, 15.8%, 16%, 16.2%, 16.5%, 16.8%, 17%, 17.2%, 17.5%, 17.8%, 18%, 18.2%, 18.5%, 18.8%, 19%, 19.2%, 19.5%, 19.8%, and 20%.
[0055] In some of these examples, in the oxide dispersion strengthened steel, the second component includes the following components by mass percentage:
[0056] Zn 4.6%~6.5%, Mg 1.8%~2.9%, Cu 1.2%~1.9%, nanoparticles 15%~20% and the balance Al.
[0057] In some examples, in the oxide dispersion strengthened steel, the oxide particles include at least one of La2O3, Y2O3, Ce2O3, TiO2, and MgO.
[0058] It can be understood that the oxide particles may contain one of La2O3, Y2O3, Ce2O3, TiO2 and MgO, or may contain two or more of La2O3, Y2O3, Ce2O3, TiO2 and MgO.
[0059] In some of these examples, the oxide particles in oxide dispersion strengthened steels have a particle size of 10 nm to 30 nm.
[0060] In some of these examples, the oxide particles in oxide dispersion strengthened steels have a particle size of 10 nm to 30 nm.
[0061] It is understood that the particle size of the oxide particles includes but is not limited to 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 28 nm, and 30 nm.
[0062] In some of these examples, the mass of the graphene layer in the oxide dispersion-strengthened steel is 40% to 60% of the total mass of the nanoparticles.
[0063] It can be understood that the percentage of the mass of the graphene layer to the total mass of the nanoparticles includes but is not limited to 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, and 60%. It can be further understood that by controlling the mass proportion of the graphene layer in the nanoparticles and combining the mass proportion of the second component in the oxide dispersion strengthened steel, the mass proportion of the graphene in the oxide dispersion strengthened steel can be obtained.
[0064] In some of these examples, in oxide dispersion strengthened steels, the mass proportion of graphene in the oxide dispersion strengthened steel is 0.3%~1.8%.
[0065] It can be understood that the mass proportion of graphene in oxide dispersion strengthened steel includes but is not limited to 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, and 1.8%.
[0066] Optionally, in the oxide dispersion strengthened steel, the mass proportion of graphene in the oxide dispersion strengthened steel is 0.7%~1.4%.
[0067] An embodiment of the present application provides a method for preparing oxide dispersion strengthened steel, comprising the following steps:
[0068] Providing powder raw materials according to the composition of the above oxide dispersion strengthened steel;
[0069] The powder materials are mixed and then molded.
[0070] It can be understood that the above-mentioned oxide dispersion strengthened steel can be prepared by the preparation method of oxide dispersion strengthened steel provided in the present application, and can also be prepared by other methods; it can be further understood that the characteristics between the oxide dispersion strengthened steel and the preparation method of oxide dispersion strengthened steel provided in the present application can be applicable to each other.
[0071] In some examples, the method for preparing oxide dispersion strengthened steel includes the following steps:
[0072] Mixing the powder raw materials of the second component to prepare an intermediate powder;
[0073] The powder raw material of the first component is mixed with the intermediate powder and Fe powder to prepare a mixed powder;
[0074] The mixed powder is molded.
[0075] In some examples, in the method for preparing oxide dispersion strengthened steel, the method for preparing nanoparticles comprises the following steps:
[0076] The graphene layer is grown on the surface of the oxide particles using chemical vapor deposition.
[0077] By in situ growing a graphene (GNPs) coating on the surface of oxide particles, the dispersion of nanoparticles in the matrix can be further improved, thereby further enhancing the high-temperature tensile strength and thermal conductivity of oxide dispersion-strengthened steel.
[0078] In some of these examples, in the method for preparing oxide dispersion strengthened steel, chemical vapor deposition includes a deposition phase and a growth phase.
[0079] In some of the examples, in the method for preparing oxide dispersion strengthened steel, the atmosphere during the deposition stage is a mixed gas of methane, hydrogen and argon.
[0080] Furthermore, in the mixed gas, the volume ratio of hydrogen, argon and methane is (10~30):(10~30):1.
[0081] It can be understood that the volume ratio of argon to methane is (10~30):1, and the volume ratio of hydrogen to methane is (10~30):1; it can be further understood that the volume ratio of argon to methane includes but is not limited to 10:1, 15:1, 20:1, 25:1, 30:1; the volume ratio of hydrogen to methane includes but is not limited to 10:1, 15:1, 20:1, 25:1, 30:1.
[0082] In some specific examples, in the method for preparing oxide dispersion strengthened steel, the volume ratio of hydrogen, argon and methane is 20:20:1.
[0083] In some of the examples, during the deposition phase, the flow rate of argon is 50 sccm~200 sccm, the flow rate of hydrogen is 50 sccm~200 sccm, and the flow rate of methane is 2 sccm~10 sccm.
[0084] It can be understood that during the deposition stage, the flow rate of argon gas includes but is not limited to 50 sccm, 80 sccm, 100 sccm, 120 sccm, 150 sccm, 180 sccm, and 200 sccm; the flow rate of hydrogen gas includes but is not limited to 50 sccm, 80 sccm, 100 sccm, 120 sccm, 150 sccm, 180 sccm, and 200 sccm; the flow rate of methane includes but is not limited to 2 sccm, 5 sccm, 8 sccm, and 10 sccm.
[0085] In some of these examples, in the preparation method of oxide dispersion strengthened steel, the temperature of the deposition stage is 300℃~400℃ and the growth time is 1 h~3 h.
[0086] It will be understood that the temperature in the deposition stage includes but is not limited to 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, and 400°C, and the growth time includes but is not limited to 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h, 2.8 h, and 3 h.
[0087] In some of these examples, in the method for preparing oxide dispersion strengthened steel, the temperature in the growth stage is 1000°C~1200°C and the growth time is 1 h~3 h.
[0088] It will be appreciated that the temperature during the growth phase includes but is not limited to 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1080°C, 1100°C, 1120°C, 1150°C, 1180°C, 1200°C, and the growth time includes but is not limited to 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h.
[0089] In some of these examples, argon gas was purged during the growth phase.
[0090] In some examples, in the method for preparing oxide dispersion strengthened steel, the method for preparing nanoparticles comprises the following steps:
[0091] Argon, hydrogen and methane gases are introduced, and the oxide particles are first heated to deposit graphene on the surface of the oxide particles; then, argon gas is continuously introduced and a second heating is performed to grow graphene, thereby obtaining nanoparticles with graphene-like layers formed on the surface of the oxide particles.
[0092] In some of the examples, in the method for preparing oxide dispersion strengthened steel, the diameter of aluminum powder in the raw material powder is 10 μm~80 μm.
[0093] It can be understood that the diameter of the aluminum powder includes but is not limited to 10 μm, 20 μm, 50 μm, and 80 μm.
[0094] In some of the examples, in the method for preparing oxide dispersion strengthened steel, the forming process includes but is not limited to one of hot isostatic pressing, hot pressing sintering and SPS sintering (spark plasma sintering).
[0095] In some of the examples, in the method for preparing oxide dispersion strengthened steel, the temperature of the forming process is 1000°C~1400°C.
[0096] It will be appreciated that the temperature of the molding process includes but is not limited to 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1080°C, 1100°C, 1120°C, 1150°C, 1180°C, 1200°C, 1250°C, 1300°C, 1350°C, and 1400°C.
[0097] In some of the examples, in the method for preparing oxide dispersion strengthened steel, the pressures of hot pressing sintering and SPS sintering are independently 50 MPa ~ 80 MPa.
[0098] In some of these examples, in the preparation method of oxide dispersion strengthened steel, the pressure of hot isostatic pressing is 100MPa ~120MPa.
[0099] In some of these examples, in the method for preparing oxide dispersion strengthened steel, the forming process time is 1 h to 3 h.
[0100] It can be understood that the time for the molding process includes but is not limited to 10 h, 11 h, 12 h, 13 h, 14 h, and 15 h.
[0101] One embodiment of the present application provides the use of the oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method in preparing steel products. Another embodiment of the present application provides a steel product, comprising the oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method.
[0102] The oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method is used to prepare steel products, which can give the steel products higher high-temperature tensile strength.
[0103] In some of these embodiments, steel products include, but are not limited to, aerospace parts, such as parts of jet engines; as structural materials in nuclear reactors; used in high temperature and high pressure equipment in the oil and gas industry, etc.
[0104] In some embodiments, the material of the steel product may be the oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method, that is, the steel product is directly prepared by using the oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method. In other embodiments, the material of the steel product may include other materials in addition to the oxide dispersion strengthened steel or the oxide dispersion strengthened steel prepared by the above preparation method.
[0105] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.
[0106] Example 1
[0107] (1) Preparation of nanoparticles
[0108] 100 sccm of argon, 100 sccm of hydrogen and 5 sccm of methane were continuously introduced into the tube furnace, MgO particles (particle size of 10 nm~15 nm) were selected as the growth substrate of graphene, and the heating temperature was adjusted to 300°C in this environment, and the gas was continuously introduced for 2 h to complete the deposition of graphene on the MgO surface; then 200 sccm of argon was continuously introduced into the tube furnace, and the heating temperature was adjusted to 1200°C in this environment, and the gas was continuously introduced for 2 h to complete the growth of graphene on the MgO surface and form a graphene-like coating, that is, to prepare MgO nanoparticles, in which the mass proportion of graphene in the nanoparticles was 40%.
[0109] (2) Preparation of oxide dispersion strengthened steel
[0110] (2.1) Provide raw materials according to the following components and proportions:
[0111] The first component is 9 wt.%, the second component is 5 wt.%, and the rest is Fe and other inevitable impurities;
[0112] Among them, the first component: Cr;
[0113] The second component: Zn 4.6 wt.%, Mg 2.4 wt.%, Cu 1.6 wt.%, MgO nanoparticles 25 wt.%, and the rest is Al;
[0114] (2.2) Mix the powder raw materials in the second component and mix them in a V-type powder mixer for more than 24 hours to obtain an intermediate powder;
[0115] (2.3) Mix the Cr, intermediate powder and Fe powder in a V-type powder mixer for more than 24 hours to obtain a mixed powder;
[0116] (2.4) The mixed powder was sintered by hot pressing at a molding temperature of 1200°C, an applied pressure of 50 MPa, and a holding time of 12 h.
[0117] Example 2
[0118] (1) Preparation of nanoparticles
[0119] 100 sccm of argon, 100 sccm of hydrogen and 5 sccm of methane were continuously introduced into the tube furnace, Y2O3 particles were selected as the growth substrate of graphene, and the heating temperature was adjusted to 400°C in this environment. The gas was continuously introduced for 2 hours to complete the deposition of graphene on the Y2O3 surface. Then, 200 sccm of argon was continuously introduced into the tube furnace, and the heating temperature was adjusted to 1000°C in this environment. The gas was continuously introduced for 2 hours to complete the growth of graphene on the Y2O3 surface and form a graphene-like coating, i.e., to prepare Y2O3 nanoparticles, in which the mass proportion of graphene in the nanoparticles was 60%.
[0120] (2) Preparation of oxide dispersion strengthened steel
[0121] (2.1) Provide raw materials according to the following components and proportions:
[0122] The first component is 14 wt.%, the second component is 10 wt.%, and the rest is Fe and other inevitable impurities;
[0123] Among them, the first component: Cr;
[0124] The second component: Zn 5.6 wt.%, Mg 1.8 wt.%, Cu 1.9 wt.%, Y2O3 nanoparticles 15 wt.%, and the rest is Al;
[0125] (2.2) Mix the powder raw materials in the second component and mix them in a V-type powder mixer for more than 24 hours to obtain an intermediate powder;
[0126] (2.3) Mix the Cr, intermediate powder and Fe powder in a V-type powder mixer for more than 24 hours to obtain a mixed powder;
[0127] (2.4) The mixed powder was sintered by SPS at a molding temperature of 1050°C, an external pressure of 50 MPa, and a holding time of 12 h.
[0128] Example 3
[0129] (1) Preparation of nanoparticles
[0130] 100 sccm of argon, 100 sccm of hydrogen and 5 sccm of methane were continuously introduced into the tubular furnace, TiO2 particles were selected as the growth substrate of graphene, and the heating temperature was adjusted to 350°C in this environment. The gas was continuously introduced for 2 hours to complete the deposition of graphene on the TiO2 surface. Then, 200 sccm of argon was continuously introduced into the tubular furnace, and the heating temperature was adjusted to 1000°C in this environment. The gas was continuously introduced for 2 hours to complete the growth of graphene on the TiO2 surface and form a graphene-like coating, i.e., prepare TiO2 nanoparticles, in which the mass proportion of graphene in the nanoparticles is 50%.
[0131] (2) Preparation of oxide dispersion strengthened steel
[0132] (2.1) Provide raw materials according to the following components and proportions:
[0133] The first component is 14 wt.%, the second component is 14 wt.%, and the rest is Fe and other inevitable impurities;
[0134] Among them, the first component: Cr;
[0135] The second component: Zn 6.1 wt.%, Mg 2.4 wt.%, Cu 1.2 wt.%, TiO2 nanoparticles 20 wt.%, and the rest is Al;
[0136] (2.2) Mix the powder raw materials in the second component and mix them in a V-type powder mixer for more than 24 hours to obtain an intermediate powder;
[0137] (2.3) Mix Cr, intermediate powder and Fe powder, mix in a V-type powder mixer for more than 24 hours to obtain a mixed powder, and then put the mixed powder into an aluminum alloy bag, vacuum degassing and sealing;
[0138] (2.4) The mixed powder was hot isostatically pressed at a molding temperature of 1400°C, an applied pressure of 110-120 MPa, and a holding time of 4 h.
[0139] Example 4
[0140] (1) Same as step (1) in Example 1;
[0141] (2.1) Provide raw materials according to the following components and proportions:
[0142] The first component is 14 wt.%, the second component is 14 wt.%, and the rest is Fe and other inevitable impurities;
[0143] Among them, the first component: Cr;
[0144] The second component: Zn 6.1 wt.%, Mg 2.4 wt.%, Cu 1.2 wt.%, MgO nanoparticles 20 wt.%, and the rest is Al;
[0145] (2.2) Mix the powder raw materials in the second component and mix them in a V-type powder mixer for more than 24 hours to obtain an intermediate powder;
[0146] (2.3) Mix Cr, intermediate powder and Fe powder, mix in a V-type powder mixer for more than 24 hours to obtain a mixed powder, and then put the mixed powder into an aluminum alloy bag, vacuum degassing and sealing;
[0147] (2.4) The mixed powder was hot isostatically pressed at a molding temperature of 1400°C, an applied pressure of 110-120 MPa, and a holding time of 4 h.
[0148] Example 5
[0149] The method is basically the same as Example 4, except that in step (2.1), the raw materials are provided according to the following components and proportions:
[0150] The first component is 14 wt.%, the second component is 10 wt.%, and the rest is Fe and other inevitable impurities;
[0151] Among them, the first component: Cr;
[0152] The second component: Zn 6.1 wt.%, Mg 2.4 wt.%, Cu 1.2 wt.%, MgO nanoparticles 20 wt.%, and the rest is Al.
[0153] Example 6
[0154] The method is basically the same as Example 4, except that in step (2.1), the raw materials are provided according to the following components and proportions:
[0155] The first component is 14 wt.%, the second component is 7 wt.%, and the rest is Fe and other inevitable impurities;
[0156] Among them, the first component: Cr;
[0157] The second component: Zn 6.1 wt.%, Mg 2.4 wt.%, Cu 1.2 wt.%, MgO nanoparticles 10 wt.%, and the rest is Al.
[0158] Example 7
[0159] The method is basically the same as Example 4, except that in step (1) of Example 7, Ce2O3 particles are selected as the growth substrate of graphene to prepare Ce2O3 nanoparticles; and in step (2.1), the MgO nanoparticles in step (2.1) of Example 7 are replaced with Ce2O3 nanoparticles of equal mass.
[0160] Comparative Example 1
[0161] The method is basically the same as Example 1, except that, in Comparative Example 1, the MgO nanoparticles in the second component of step (2.1) of Example 1 are replaced by MgO particles used as the graphene growth substrate in step (1) of Example 1, that is, no graphene-like coating is formed on the surface of the MgO particles used in Comparative Example 1.
[0162] Comparative Example 2
[0163] The method is basically the same as Example 1, except that no MgO nanoparticles are added in the preparation of the oxide dispersion strengthened steel.
[0164] Comparative Example 3
[0165] The method is basically the same as Example 1, except that in step (2.1), the raw materials are provided according to the following components and proportions:
[0166] The first component is 9 wt.%, the second component is 20 wt.%, and the rest is Fe and other inevitable impurities;
[0167] Among them, the first component: Cr;
[0168] The second component: Zn 4.6 wt.%, Mg 2.4 wt.%, Cu 1.6 wt.%, MgO nanoparticles 25 wt.%, and the rest is Al.
[0169] Comparative Example 4
[0170] The method is basically the same as Example 1, except that in step (2.1), the raw materials are provided according to the following components and proportions:
[0171] The first component is 14 wt.%, the second component is 14 wt.%, and the rest is Fe and other inevitable impurities;
[0172] Among them, the first component: Cr;
[0173] The second component: Zn 4.6 wt.%, Mg 2.4 wt.%, Cu 1.6 wt.%, MgO nanoparticles 5 wt.%, and the rest is Al.
[0174] Comparative Example 5
[0175] The method is basically the same as Example 1, except that in step (2.1), the raw materials are provided according to the following components and proportions:
[0176] The first component is 9 wt.%, the second component is 5 wt.%, and the rest is Fe and other inevitable impurities;
[0177] Among them, the first component: Cr;
[0178] The second component: Ni 4.6 wt.%, Mg 2.4 wt.%, Cu 1.6 wt.%, MgO nanoparticles 8 wt.%, and the rest is Al.
[0179] Comparative Example 6
[0180] (1) Provide raw materials according to the following components and proportions:
[0181] The first component is 9 wt.%, the second component is 5 wt.%, and the rest is Fe and other inevitable impurities;
[0182] Among them, the first component: Cr;
[0183] The second component: Zn 4.6 wt.%, Mg 2.4 wt.%, Cu 1.6 wt.%, MgO particles 8 wt.%, graphene sheets 2 wt.%, and the rest is Al;
[0184] (2) Mix the powder raw materials in the second component and mix them in a V-type powder mixer for more than 24 hours to obtain an intermediate powder;
[0185] (3) Mixing Cr, intermediate powder and Fe powder in a V-type powder mixer for more than 24 hours to obtain a mixed powder;
[0186] (4) The mixed powder was hot pressed and sintered at a molding temperature of 1200°C, an applied pressure of 50 MPa, and a holding time of 12 h to prepare oxide dispersion strengthened steel.
[0187] The composition of the oxide dispersion strengthened steel in each embodiment and comparative example is shown in Table 1.
[0188] Table 1
[0189]
[0190] The “total amount” in Table 2 refers to the proportion of the second component in the oxide dispersion strengthened steel.
[0191] The oxide dispersion strengthened steels prepared in each embodiment and comparative example were respectively subjected to tensile strength tests (room temperature GB / T228.1-2021; 700°C GB / T 228.2-2015) and electrical conductivity (ISO 22007-2). The test results are shown in Table 2.
[0192] Table 2
[0193]
[0194] It can be seen from Table 2 that, compared with the comparative examples, the oxide dispersion strengthened steel prepared in the embodiments has higher tensile strength at room temperature and high temperature conditions, and better thermal conductivity; among them, in comparative example 6, MgO particles and graphene sheets without a graphene-like coating on the surface are added to the second component, and the high-temperature tensile strength is not as good as that of comparative example 2 without adding MgO nanoparticles. This is because the direct addition of graphene sheets to the second component in comparative example 6 will cause agglomeration.
[0195] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0196] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. An oxide dispersion strengthened steel, characterized in that: Calculated by mass percentage, it includes 9% to 15% of the first component, 5% to 15% of the second component, and the remainder of Fe and unavoidable impurities; wherein the first component comprises Cr; The second component comprises the following components by mass percentage: Zn 4%-8%, Mg 1%-4%, Cu 1%-3%, nanoparticles 15%-25% and the balance Al; the nanoparticles are oxide particles having a graphene layer on the surface.
2. The oxide dispersion strengthened steel according to claim 1, characterized in that: The mass ratio of the first component to the second component is (1~2):
1.
3. The oxide dispersion strengthened steel according to claim 1, characterized in that: The mass of the nanoparticles accounts for 15% to 20% of the total mass of the second component.
4. The oxide dispersion strengthened steel according to claim 1, characterized in that: The second component comprises the following components by mass percentage: Zn 4.6%~6.5%, Mg 1.8%~2.9%, Cu 1.2%~1.9%, nanoparticles 15%~20% and the balance Al.
5. The oxide dispersion strengthened steel according to any one of claims 1 to 4, characterized in that: The oxide particles include at least one of La2O3, Y2O3, Ce2O3, TiO2 and MgO.
6. The oxide dispersion strengthened steel according to any one of claims 1 to 4, characterized in that: The particle size of the oxide particles is 10 nm to 30 nm, and the mass of the graphene layer is 40% to 60% of the total mass of the nanoparticles.
7. A method for preparing oxide dispersion strengthened steel, characterized in that: The following steps are involved: Providing a powder raw material according to the composition of the oxide dispersion strengthened steel according to any one of claims 1 to 6; The powder raw materials are mixed and then molded.
8. The preparation method according to claim 7, characterized in that: The method for preparing the nanoparticles comprises the following steps: A graphene layer is grown on the surface of the oxide particles by chemical vapor deposition.
9. The preparation method according to claim 8, characterized in that: The chemical vapor deposition includes a deposition phase and a growth phase, and the chemical vapor deposition satisfies at least one of the following characteristics: (1) The atmosphere during the deposition stage is a mixed gas of methane, hydrogen and argon; (2) The temperature of the deposition stage is 300°C to 400°C, and the growth time is 1 h to 3 h; (3) The temperature of the growth stage is 1000°C to 1200°C, and the growth time is 1 h to 3 h.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The temperature of the molding process is 1000°C to 1400°C.
11. Use of the oxide dispersion strengthened steel according to any one of claims 1 to 6 or the oxide dispersion strengthened steel prepared by the preparation method according to any one of claims 7 to 10 in the preparation of steel products.
12. A steel product, characterized in that: It comprises the oxide dispersion strengthened steel as described in any one of claims 1 to 6 or the oxide dispersion strengthened steel prepared by the preparation method as described in any one of claims 7 to 10.